2023
DOI: 10.1002/anie.202217130
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Sulfoximines via Iridium‐Catalyzed Regio‐ and Enantioselective C−H Borylation: A Remarkable Sidearm Effect of Ligand

Abstract: Transition metal‐catalyzed enantioselective C−H activation of prochiral sulfoximines for non‐annulated products remains a formidable challenge. We herein report iridium‐catalyzed enantioselective C−H borylation of N‐silyl diaryl sulfoximines using a well‐designed chiral bidentate boryl ligand with a bulky side arm. This method is capable of accommodating a broad range of substrates under mild reaction conditions, affording a vast array of chiral sulfoximines with high enantioselectivities. We also demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 86 publications
1
33
0
Order By: Relevance
“…[73] We found that helical assemblies of Pt(II) complexes became CPL-active with appreciable g lum values. [42] The CPL activity differs from those of multi-luminophore molecular systems that experience asymmetric exciton coupling, [26,[74][75][76][77][78][79][80][81][82][83][84][85][86] in that it is attributed to the non-orthogonal orientation between μ and m. [67,87,88] Moreover, the strong spin-orbit coupling offered by the two Pt centers could enhance m. [89] These characteristics could collectively contribute to improved chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[73] We found that helical assemblies of Pt(II) complexes became CPL-active with appreciable g lum values. [42] The CPL activity differs from those of multi-luminophore molecular systems that experience asymmetric exciton coupling, [26,[74][75][76][77][78][79][80][81][82][83][84][85][86] in that it is attributed to the non-orthogonal orientation between μ and m. [67,87,88] Moreover, the strong spin-orbit coupling offered by the two Pt centers could enhance m. [89] These characteristics could collectively contribute to improved chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Purely organic room temperature phosphorescence (RTP) materials have attracted tremendous attention and have seen rapid development in the past decade. [1][2][3][4][5][6][7] Being less expensive, more flexible and stable to moisture compared to their organometallic counterparts, these materials have found applications in various technologies such as anticounterfeiting, [8][9][10][11] encryption, [12][13] bioimaging [14][15][16][17][18][19] and optoelectronics. [20][21][22] According to the first-order perturbation theory, the rate of intersystem crossing (ISC), the first step for RTP, is proportional to the spin-orbit coupling (SOC) matrix element and the reciprocal of energy gap between the excited singlet and triplet states ( ~EST ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, organic persistent room-temperature phosphorescent (RTP) materials have attracted significant attention owing to their unique long-lived luminescent properties, rendering them suitable for a broad array of optoelectronic applications. [1][2][3][4] Despite the development of various groundbreaking strategies, such as crystal engineering, [5][6][7][8] polymerization, [9][10][11] and host-guest doping, [12][13][14] which have led to persistent RTP materials with diverse phosphorescence colors, [15,16] high quantum efficiencies, [17,18] and long emission decay times, [13,19] the advancement of stimuli-responsive RTP materials remains a compelling challenge. These materials have the ability to dynamically modulate their persistent RTP properties in response to microenvironmental changes.…”
Section: Introductionmentioning
confidence: 99%